Multifonctionnalité des espaces végétalisés urbains - Wissal Selmi; Christiane Weber; Lotfi Mehdi (VertigO)
Urban green spaces, considered as a “green showcase”, have been the topic of numerous scientific researches during the past 20 years, investigating not only its socio-urban values but also its ecological ones (Clergeau, 2012). Nowadays, some new concepts are associated to urban green spaces, such as the “multifunctionality” and “ecosystem services” concepts (Bastian et al., 2011). However, the lack of terminological consensus of these concepts limits their use and their integration in the decision-making processes. Based on a literature review, this paper aims to investigate how the scientific community takes into account these concepts. Moreover, we discuss the current conceptual framework in order to highlight some wording imprecision. Finally, we provide further guidance for the creation of future urban greenway.